1977
DOI: 10.1111/j.1432-1033.1977.tb11588.x
|View full text |Cite
|
Sign up to set email alerts
|

Specific Casein Phosphorylation by a Casein Kinase from Lactating Bovine Mammary Gland

Abstract: 1. A preparation which contains protein kinase activity capable of rephosphorylating dephosphorylated @,I and P-caseins has been prepared from lactating bovine mammary gland. This activity is localised in the Golgi fraction and in this respect is similar to that obtained previously from rat tissue. It differs from the rat preparation in being unable to rephosphorylate dephosphorylated x-casein.2. Progressive dephosphorylation of asl and P-caseins increases the rate of their rephosphorylation in the presence bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

1981
1981
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…A protein kinase has been isolated from the Golgi fraction of breast tissue from lactating guinea pigs (Moore et al, 1985) and cows (MacKinlay et al, 1977), which, in studies carried out using peptide substrates, proved to be specific for serine residues in Ser-X-Glu/Ser(P) sequences (Meggio et al, 1988). This enzyme appears to be the best candidate for the protein kinase that phosphorylates the proteins that are secreted into milk, namely the caseins and PP3.…”
Section: The Sxe-specific Protein Kinasementioning
confidence: 99%
“…A protein kinase has been isolated from the Golgi fraction of breast tissue from lactating guinea pigs (Moore et al, 1985) and cows (MacKinlay et al, 1977), which, in studies carried out using peptide substrates, proved to be specific for serine residues in Ser-X-Glu/Ser(P) sequences (Meggio et al, 1988). This enzyme appears to be the best candidate for the protein kinase that phosphorylates the proteins that are secreted into milk, namely the caseins and PP3.…”
Section: The Sxe-specific Protein Kinasementioning
confidence: 99%
“…Guinea-pig caseins were prepared as described previously [8], and either used directly as substrate, or dephosphorylated using potato acid phosphatase at a final concentration of 2 units/ml essentially as described by Bingham and coworkers [I 81. Dephosphorylated casein was recovered according to the method of Mackinlay et al [19]. This procedure resulted in complete ( 2 95 %) dephosphorylation of guinea-pig caseins as judged by dephosphorylation of a mixture of 32P-labelled caseins (20000 counts/min) which had been synthesized and secreted by guinea-pig mammary gland explants in culture, in the presence of 100 pg total guinea-pig casein carrier isolated from milk.…”
Section: Enzyme Assaysmentioning
confidence: 99%
“…Although the detailed structure of these micelles has not been fully elucidated, it is known that the presence of Ca2+ and the phosphorylation of certain serine residues in caseins are prerequisites for micelle formation [2 -61. In the mammary gland secretory cell, this phosphorylation occurs during passage of the caseins from their sites of synthesis on rough endoplasmic reticulum to the alvaeolar lumen, most probably within cisternae and vesicles of the Golgi apparatus Identification and characterization of the protein kinase(s) responsible for the physiological phosphorylation of caseins has been complicated by the fact that Golgi-associated protein kinase activity accounts for only a small proportion of the total protein kinase activity of lactating mammary tissue [8,91. Nevertheless, Bingham and co-workers [lo -151 have reported that Golgi vesicle preparations from both rat and bovine mammary glands contain protein kinases capable of phosphorylating bovine caseins, and a similar kinase activity has been demonstrated in Golgi vesicles isolated from guinea pig mammary glands [16].…”
mentioning
confidence: 99%